INTERNET OF THINGS (IOT) BASED SMART CHOPPER SYSTEM WITH WEIGHT MONITORING TO IMPROVE PRODUCTIVITY - Rudy Mustaqim; Irma Salamah; Ahmad Taqwa (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
The food processing industry faces challenges in enhancing efficiency and productivity, particularly in raw material processing. This research addresses the limitations of manual cutting processes, which lead to inconsistencies, human error, and prolonged production times. By integrating Internet of Things (IoT) technology into a smart chopper system with weight monitoring, the study aims to automate cutting speed, reduce waste, and improve product quality. The developed system incorporates sensors for weight measurement and voltage monitoring, controlled by an ESP32 microcontroller for real-time adjustments and monitoring. The system’s performance was evaluated based on material hardness and weight, demonstrating its ability to optimize cutting processes and provide consistent results. The IoT integration enables remote control and monitoring, enhancing productivity, reducing waste, and ensuring seasoning quality in the food processing industry.